Sealant composition and tire using same
Patent Information
- Application Number
- JP2023219314
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2043-12-26
AI Technical Summary
【0007】 本発明のシーラント材組成物は、(A)天然ゴムおよび/または合成イソプレンゴム50~100質量部、並びに、スチレン-ブタジエン共重合体ゴム、ブタジエンゴムまたはこれらの混合物0~50質量部からなるゴム成分に対し、(B)加硫促進剤および(C)硫黄を配合するとともに、前記(B)加硫促進剤/前記(C)硫黄(質量比)を2.5以上に設定している。前記(B)加硫促進剤/前記(C)硫黄(質量比)を2.5以上にすることにより、初期または劣化後の適切な流れ性が確保される。また、例えば経時劣化に伴ってシーラント材組成物の架橋による硬化が進行しても、前記(A)ゴム成分の主成分である天然ゴムおよび/または合成イソプレンゴムの軟らかさが前記架橋による硬化を補い、結果としてシーラント材組成物の粘着力の低減やシュリンクを抑制でき、劣化後の剥がれも十分に抑制できるものと推測される。
Smart Images

Figure 0007648941000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a sealant composition and a tire using the same. [Background technology]
[0002] There is known a pneumatic tire having a sealant layer provided on the radially inner side of an inner liner layer in a tread portion of the tire. In such a pneumatic tire, when a foreign object such as a nail penetrates the tread portion, the sealant composition flows into the through hole, thereby exerting a sealing property and suppressing a decrease in air pressure, thereby enabling the tire to continue running. The sealant material compositions are disclosed, for example, in the following Patent Documents 1 to 4. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5646474 [Patent Document 2] Patent No. 5651109 [Patent Document 3] Patent No. 5525522 [Patent Document 4] Patent No. 5738897 Summary of the Invention [Problem to be solved by the invention]
[0004] The sealant composition is required to have flowability to ensure sealing performance and not to peel off due to deterioration caused by traveling. It has been found that the peeling occurs due to the progress of curing due to crosslinking of the sealant composition due to deterioration, which reduces the adhesive strength and causes shrinkage of the sealant composition. However, the conventional techniques have room for improvement in terms of flowability at the initial stage or after deterioration, and in terms of peeling. An object of the present invention is to solve the above problems and to provide a sealant composition that ensures appropriate flowability initially or after deterioration and can sufficiently suppress peeling after deterioration, and a tire using the same. [Means for solving the problem]
[0005] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by a sealant composition in which a vulcanization accelerator and sulfur are blended with a rubber component having a specific composition, and the blending ratio of the vulcanization accelerator and the sulfur is specified, and have thus completed the present invention.
[0006] That is, the present invention provides a sealant material composition for forming a sealant layer of a pneumatic tire having a sealant layer on the inner surface of the tire, comprising: (A) a rubber component consisting of 50 to 100 parts by mass of natural rubber and / or synthetic isoprene rubber, and 0 to 50 parts by mass of styrene-butadiene copolymer rubber, butadiene rubber, or a mixture thereof; (B) a vulcanization accelerator, and (C) Sulfur and the (B) vulcanization accelerator / (C) sulfur (mass ratio) is 2.5 or more. The present invention provides a sealant material composition comprising: Effect of the Invention
[0007] The sealant composition of the present invention is prepared by compounding (B) a vulcanization accelerator and (C) sulfur with a rubber component consisting of (A) 50 to 100 parts by mass of natural rubber and / or synthetic isoprene rubber, and 0 to 50 parts by mass of styrene-butadiene copolymer rubber, butadiene rubber, or a mixture thereof, and setting the (B) vulcanization accelerator / (C) sulfur (mass ratio) to 2.5 or more. By setting the (B) vulcanization accelerator / (C) sulfur (mass ratio) to 2.5 or more, appropriate flowability is ensured at the initial stage or after deterioration. In addition, even if the sealant composition progresses in hardening due to crosslinking with deterioration over time, for example, the softness of the natural rubber and / or synthetic isoprene rubber, which is the main component of the (A) rubber component, compensates for the hardening due to the crosslinking, and as a result, it is presumed that the sealant composition can be prevented from reducing its adhesive strength or shrinking, and peeling after deterioration can be sufficiently prevented. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention will now be described in further detail. (A) Rubber component The rubber component (A) used in the present invention is mainly composed of natural rubber (NR) and / or synthetic isoprene rubber (IR). The rubber component (A) may also contain styrene-butadiene copolymer rubber (SBR), butadiene rubber (BR), or a mixture thereof. The rubber component (A) may be terminally modified with amine, amide, silyl, alkoxysilyl, carboxyl, hydroxyl, or the like, or may be epoxidized. The weight average molecular weight (Mw) of the rubber component (A) is not particularly limited, but for reasons such as better effects of the present invention, it is preferably 100,000 to 5,000,000, more preferably 200,000 to 3,000,000, and even more preferably 300,000 to 2,000,000. In this specification, the weight average molecular weight (Mw) and number average molecular weight (Mn) are values calculated as standard polystyrene by gel permeation chromatography (GPC).
[0009] The rubber component (A) used in the present invention contains 50 to 100 parts by mass, preferably 50 to 80 parts by mass of NR and / or IR, and 0 to 50 parts by mass, preferably 20 to 50 parts by mass of SBR, BR or a mixture thereof, based on 100 parts by mass of the entire rubber component.
[0010] (B) vulcanization accelerator and (C) sulfur Examples of the vulcanization accelerator (B) used in the present invention include known sulfenamide-based, thiazole-based, guanidine-based, thiourea-based, dithiocarbamate-based, xanthogenate-based, and thiuram-based vulcanization accelerators, and among them, from the viewpoint of improving the effects of the present invention, one or more types selected from the group consisting of sulfenamide-based vulcanization accelerators and thiazole-based vulcanization accelerators are preferred. The sealant composition of the present invention is capable of dynamic crosslinking since it contains sulfur (C).
[0011] (Mixing ratio of sealant composition) In the sealant composition of the present invention, the amount of the vulcanization accelerator (B) mixed is, for example, 1 to 5 parts by mass, preferably 1 to 4 parts by mass, and more preferably 1 to 3 parts by mass, per 100 parts by mass of the rubber component (A). In the sealant composition of the present invention, the amount of (C) sulfur is, for example, less than 0.5 parts by mass, preferably 0.1 to 0.4 parts by mass, and more preferably 0.15 to 0.3 parts by mass, per 100 parts by mass of the (A) rubber component. In the sealant material composition of the present invention, the (B) vulcanization accelerator / (C) sulfur (mass ratio) must be 2.5 or more. If the ratio is less than 2.5, it is not possible to ensure appropriate flowability at the initial stage or after deterioration, and it is not possible to sufficiently suppress peeling after deterioration. The (B) vulcanization accelerator / (C) sulfur (mass ratio) is preferably 5 or more, more preferably 10 or more, and particularly preferably 10 to 20. When the blending ratio is within the preferred range, the effects of the present invention are more favorably exhibited.
[0012] From the viewpoint of improving the effect, the sealant composition of the present invention preferably contains magnesium oxide, and the BET specific surface area of the magnesium oxide is preferably 20 to 200 m. 2 The BET specific surface area of magnesium oxide is the specific surface area of magnesium oxide measured by the single point method of JIS Z8830, determined by adsorption of nitrogen gas. The blending amount of the magnesium oxide is, for example, less than 1.0 part by mass, and preferably 0.1 to 0.5 part by mass, per 100 parts by mass of the (A) rubber component.
[0013] The sealant material composition of the present invention can be blended with a tackifier as a suitable form. Examples of tackifiers include hydrocarbon resins. Examples of hydrocarbon resins include petroleum-based resins such as aromatic hydrocarbon resins produced by polymerizing components obtained by processing crude oil such as distillation, cracking, and modification, or saturated or unsaturated aliphatic hydrocarbon resins. Examples of petroleum-based resins include C5 petroleum resins (aliphatic petroleum resins obtained by polymerizing fractions such as isoprene, 1,3-pentadiene, cyclopentadiene, methylbutene, and pentene), C9 petroleum resins (aromatic petroleum resins obtained by polymerizing fractions such as α-methylstyrene, o-vinyltoluene, m-vinyltoluene, and p-vinyltoluene), and C5C9 copolymerized petroleum resins. The glass transition temperature (Tg) of the hydrocarbon resin is preferably higher than 0° C. By specifying Tg in this manner, flowability is improved. The glass transition temperature (Tg) referred to in the present invention refers to the midpoint temperature of the transition region measured by differential scanning calorimetry (DSC) at a temperature rise rate of 20° C. / min. More preferably, the Tg is 30° C. or higher and 90° C. or lower. The number average molecular weight of the hydrocarbon resin is preferably 400 to 2000. By having the number average molecular weight in this range, the adhesive strength is improved. The amount of the hydrocarbon resin mixed is preferably 10 to 90 parts by mass, and more preferably 20 to 60 parts by mass, per 100 parts by mass of the rubber component (A).
[0014] In addition, the sealant material composition of the present invention can preferably contain an inorganic filler, such as one or more selected from calcium carbonate, talc, and clay. The amount of the inorganic filler mixed is preferably 1 to 20 parts by mass, and more preferably 5 to 15 parts by mass, based on 100 parts by mass of the rubber component (A).
[0015] (Other ingredients) The sealant composition of the present invention may contain various additives such as vulcanizing or crosslinking agents, vulcanizing or crosslinking accelerators, zinc oxide, antioxidants, and plasticizers other than the above-mentioned components, and these additives may be kneaded to prepare a composition by a general method. The amounts of these additives may be conventional amounts as long as they do not go against the object of the present invention. When a plasticizer is added, it is preferably 20 to 90 parts by mass per 100 parts by mass of the (A) rubber component.
[0016] The sealant composition of the present invention can be provided as a sealant layer on the inner side of the inner liner layer in the tread portion of a pneumatic tire in the tire radial direction. The sealant layer can be formed by attaching a sealant composed of the sealant composition of the present invention molded into a sheet shape to the entire circumference of the inner surface of the tire. Alternatively, the sealant layer can be formed by attaching a sealant composed of the sealant composition of the present invention molded into a string or band shape to the inner surface of the tire in a spiral shape. The sealant can be a vulcanizate. When a foreign object such as a nail penetrates the tread portion, the sealant that constitutes the sealant layer flows into the through hole, thereby suppressing the decrease in air pressure and enabling the vehicle to continue running. The sealant layer has a thickness of, for example, 0.5 mm to 5.0 mm. EXAMPLES
[0017] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the following examples, "parts" means "parts by mass".
[0018] Examples 1 to 15 and Comparative Examples 1 to 2 The rubber composition was obtained by kneading the components (parts by mass) shown in Table 1 for 40 minutes in a 1.7-liter closed Banbury mixer. The rubber composition obtained was then press-vulcanized in a specified mold at 180°C for 10 minutes to obtain a sealant material with a thickness of 3 mm. Hereinafter, the obtained sealant material is referred to as the initial sealant material. The initial sealant obtained above was subjected to moist heat aging under the following conditions. Hereinafter, the obtained sealant is referred to as the sealant after moist heat aging. Humidity and heat deterioration conditions: Temperature 70℃, relative humidity 96%, period 30 days The following properties were examined for the initial sealant material and the sealant material after moist heat aging.
[0019] Flowability (creep) Creep measurements were carried out under the following conditions: Measurement equipment: TA Instruments dynamic viscoelasticity measuring instrument ARES-G2 Jig: 8mm diameter parallel plate Sample thickness: 1.2 mm Shear stress: 3000Pa Duration: 60 minutes If the creep is less than 100, the degree of hardening is large, the flowability is reduced, and the sealing performance cannot be maintained. On the other hand, if the creep is more than 9000, the flowability is excessive, causing problems such as flowing toward the center of the tire tread width direction while driving. The unit of creep is %.
[0020] Flowability and peeling properties (actual vehicle evaluation) In a pneumatic tire having a tire size of 215 / 55R17, with a tread portion, a pair of sidewall portions, and a pair of bead portions, and having a sealant layer made of a sealant material on the tire radial direction inside of the inner liner layer in the tread portion, the above sealant material was applied as the sealant layer to produce various test tires. The following tests were performed on the obtained test tires. The test tire immediately after production is called the initial test tire, and the test tire that was subjected to the aging treatment under the above-mentioned moist heat aging conditions is called the moist heat aging test tire.
[0021] Flowability (actual vehicle evaluation) The test tire was mounted on a wheel with a rim size of 17x7J and attached to a drum testing machine, and a high-deflection test was performed for 80 hours with an air pressure of 160kPa, a load of 8.5kN, and a running speed of 80km / h. The sealant was then examined for flow and peeling. The evaluation results were as follows: when the thickness of the 3mm sealant was 1.5mm or less at each position from the sealant end after the test, the sealant was deemed to have flowed; when no flow was observed at a position 0.5cm from the sealant end, it was indicated by "◎", when no flow was observed at a position 1cm from the sealant end, it was indicated by "○", when flow was observed at a position 1cm from the sealant end and no flow was observed at a position 2cm from the sealant end, it was indicated by "△", and when flow was observed at a position 2cm from the sealant end, it was indicated by "×".
[0022] Peelability After the flowability test (evaluation on an actual vehicle), the sealant was visually inspected for peeling. The peeling property was evaluated for the test tires after aging under moist heat.
[0023] The results are shown in Table 1.
[0024] [Table 1]
[0025] *1:NR(SIR20) *2: SBR (Nipol 1502 manufactured by Zeon Corporation) *3: Hydrocarbon resin (T-REZ RC115, C5 petroleum resin manufactured by ENEOS Corporation) *4: Naphthenic oil (Diana Process Oil NP250 (naphthenic process oil) manufactured by Idemitsu Kosan Co., Ltd.) *5: Sulfur (Kinka-jirushi oil-filled fine sulfur manufactured by Tsurumi Chemical Industry Co., Ltd.) *6: Sulfenamide vulcanization accelerator CZ (Noccela CZ-G, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) *7: Sulfenamide vulcanization accelerator NS (product name Noccela NS-P, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) *8: Thiazole-based vulcanization accelerator DM (Sanceler DM-PO manufactured by Sanshin Chemical Industry Co., Ltd.) *9: Calcium carbonate (manufactured by Maruo Calcium Co., Ltd.) *10: Magnesium oxide-1 (Kyowamag 30 manufactured by Kyowa Chemical Industry Co., Ltd., BET specific surface area = 42 m 2 / g) *11: Magnesium oxide-2 (Kyowa Chemical Industry Co., Ltd., Kyowamag 150, BET specific surface area = 144 m 2 / g)
[0026] From the results in Table 1, it was found that the sealant material composition of each Example contains (A) a rubber component consisting of 50 to 100 parts by mass of natural rubber and / or synthetic isoprene rubber, and 0 to 50 parts by mass of a styrene-butadiene copolymer rubber, a butadiene rubber, or a mixture thereof, (B) a vulcanization accelerator, and (C) sulfur, and since the (B) vulcanization accelerator / (C) sulfur (mass ratio) is 2.5 or more, appropriate flowability is ensured initially or after deterioration, and peeling after deterioration can be sufficiently suppressed. In contrast, in Comparative Example 1, the (B) vulcanization accelerator / (C) sulfur (mass ratio) was 2.0, so that the flowability after moist heat aging in the actual vehicle evaluation deteriorated, and peeling of the sealant was also observed after moist heat aging. In Comparative Example 2, the (B) vulcanization accelerator / (C) sulfur (mass ratio) was 1.7, and therefore the initial flowability of the sealant material was deteriorated in both creep and actual vehicle evaluation.
[0027] The present invention includes the following embodiments. Embodiment 1: A sealant material composition constituting a sealant layer of a pneumatic tire having a sealant layer on an inner surface of the tire, comprising: (A) a rubber component consisting of 50 to 100 parts by mass of natural rubber and / or synthetic isoprene rubber, and 0 to 50 parts by mass of styrene-butadiene copolymer rubber, butadiene rubber, or a mixture thereof; (B) a vulcanization accelerator, and (C) Sulfur and the (B) vulcanization accelerator / (C) sulfur (mass ratio) is 2.5 or more. A sealant material composition comprising: Embodiment 2: The sealant material composition according to embodiment 1, wherein the (B) vulcanization accelerator is a sulfenamide-based and / or thiazole-based vulcanization accelerator. Embodiment 3: The sealant material composition according to embodiment 1 or 2, wherein the (B) vulcanization accelerator / (C) sulfur (mass ratio) is 5 or more. Embodiment 4: 4. The sealant material composition according to any one of embodiments 1 to 3, wherein the (B) vulcanization accelerator / (C) sulfur (mass ratio) is 10 or more. Embodiment 5: 5. The sealant material composition according to any one of embodiments 1 to 4, further comprising magnesium oxide, the amount of the magnesium oxide being less than 1.0 part by mass per 100 parts by mass of the rubber component. Embodiment 6: 6. The sealant material composition according to any one of embodiments 1 to 5, wherein the blended amount of the (C) sulfur is less than 0.5 parts by mass based on 100 parts by mass of the rubber component. Embodiment 7: The sealant material composition according to any one of embodiments 1 to 6, further comprising a hydrocarbon resin as a tackifier, and the amount of the hydrocarbon resin is 10 to 90 parts by mass per 100 parts by mass of the (A) rubber component. Embodiment 8: 8. The sealant material composition according to any one of embodiments 1 to 7, further comprising at least one inorganic filler selected from calcium carbonate, talc, and clay. Embodiment 9: A tire using the sealant material composition according to any one of the first to eighth embodiments.
Claims
1. A sealant material composition constituting a sealant layer of a pneumatic tire having a sealant layer on an inner surface of the tire, comprising: (A) a rubber component consisting of 50 to 100 parts by mass of natural rubber and / or synthetic isoprene rubber, and 0 to 50 parts by mass of styrene-butadiene copolymer rubber, butadiene rubber, or a mixture thereof; (B) a vulcanization accelerator, and (C) Sulfur and the (B) vulcanization accelerator / (C) sulfur (mass ratio) is 2.5 or more. A sealant material composition comprising:
2. 2. The sealant material composition according to claim 1, wherein the vulcanization accelerator (B) is a sulfenamide-based and / or thiazole-based vulcanization accelerator.
3. 2. The sealant material composition according to claim 1, wherein the ratio of the vulcanization accelerator (B) to the sulfur (C) (mass ratio) is 5 or more.
4. 2. The sealant material composition according to claim 1, wherein the ratio (mass ratio) of the vulcanization accelerator (B) to the sulfur (C) is 10 or more.
5. 2. The sealant material composition according to claim 1, further comprising magnesium oxide, the content of the magnesium oxide being less than 1.0 part by mass per 100 parts by mass of the rubber component.
6. 2. The sealant composition according to claim 1, wherein the blending amount of the sulfur (C) is less than 0.5 parts by mass based on 100 parts by mass of the rubber component.
7. The sealant material composition according to claim 1, further comprising a hydrocarbon resin as a tackifier, and the amount of the hydrocarbon resin is 10 to 90 parts by mass per 100 parts by mass of the rubber component (A).
8. 2. The sealant material composition according to claim 1, further comprising at least one inorganic filler selected from the group consisting of calcium carbonate, talc and clay.
9. A tire using the sealant material composition according to claim 1.
Citation Information
Patent Citations
Combustion chamber in direct injection type diesel engine
JP1980025522A
Magnetic sensor for iron loss measurement of magnetic material
JP1981046474A
Frequency divider
JP1981051109A
Liquid detergent composition
JP1982038897A
Pneumatic tire and its manufacturing method
JP2019073256A